Undercover investigation - Brandev, Atanas (Law Journal of New Bulgarian University, 2023)
The use of the method of investigating and documenting criminal activity through undercover officers is a new method aimed at actively countering organized crime. The method is still not widely used in the Republic of Bulgaria.